1990
DOI: 10.5962/bhl.title.141868
|View full text |Cite
|
Sign up to set email alerts
|

Fishes of the southern ocean

Abstract: In recent years, and especially since the initiation of the BIOMASS (Biological Investigations of Marine Antarctic Systems and Stocks) Programme ten years ago, a large amount of information on the taxonomy and biology of Antarctic fishes has accumulated in many laboratories and institutions the world over. This, together with the fact that the last revisionary review of Antarctic fishes was produced by J.R. Norman (1938) more than half a century ago, was reason enough to undertake the production of a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
2
10

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(198 citation statements)
references
References 306 publications
6
180
2
10
Order By: Relevance
“…Also the anal fin showed the range of ray counts ( 30 -34) to be wider than that reported by and . The pectoral fin, too, had in the present study a wider range of ray counts ( 21 -24) than 21 -23 reported by Norman ( 1938) and Gon ( 1990).…”
Section: Discussioncontrasting
confidence: 36%
“…Also the anal fin showed the range of ray counts ( 30 -34) to be wider than that reported by and . The pectoral fin, too, had in the present study a wider range of ray counts ( 21 -24) than 21 -23 reported by Norman ( 1938) and Gon ( 1990).…”
Section: Discussioncontrasting
confidence: 36%
“…Por circunstâncias diversas e pelas adaptações que os animais que lá vivem apresentam, escolhemos a Antártica. Procurando espécies que tivessem uma distribuição nas grandes latitudes, podendo assim comparar animais colhidos numa região sub-antártica (Ilha Rei George), com fauna antártica (Fischer & Hureau 1985, Gon & Heemstra 1990). …”
Section: Porque Estudar a Imunidade Inespe-cífica Em Animais Antárticosunclassified
“…Given its wide Antarctic circumpolar distribution, D. eleginoides is caught mainly around the southern cone of America, the Falkland/Malvinas islands, South Georgia Island, and numerous other islands and oceanic elevations (Gon & Heemstra, 1990). A large part of the distribution of this resource is located in the Sub Antarctic and the Antarctic and its exploitation therein is regulated by the standards adopted by the Convention for the Conservation of Live Antarctic Marine Resources (CCRVMA).…”
Section: Introductionmentioning
confidence: 99%